Genetic diversity in the Neotropical river otter, Lontra longicaudis (Mammalia, Mustelidae), in the Lower Delta of Parana River, Argentina and its relation with habitat suitability - Trigila, Anabella Paola (2015)
Lontra longicaudis is a top predator of freshwater systems currently categorized as ‘data deficient’ by the IUCN. Thus far, no genetic studies have been carried out in Argentina. Using 8 microsatellite loci, we analysed the genetic diversity and individual relatedness in a population located at the Lower Delta of Paraná River, Argentina. Our data, together with available genetic information for other populations and habitat suitability data obtained from species distribution models previously published, were used to test whether genetic diversity, inbreeding, and parentage coefficients are related to habitat suitability both at landscape and at regional scale. Our results show that the levels of heterozygosity found in the Lower Delta are lowest reported to date. A low overall degree of relatedness between otter dyads was found. However, almost 20% showed relatedness values higher than 0.25, suggesting local reproduction. Finally, we found a positive association between habitat quality and levels of heterozygosity, both at landscape and regional scale, suggesting that in highly suitable habitats, the otters are genetically more variable. Our study constitutes the first one on the genetics of L. longicaudis in Argentina and provides baseline information for the development of conservation plans for the Lower Paraná River Delta population.